Combined Warmup Exerts an Ergogenic Effect on the Speed of Sprint Swimmers: A Systematic Review with Meta-Analysis; [el Calentamiento Combinado Ejerce Un Efecto Ergogénico Sobre la Velocidad de Los Nadadores Velocistas: Una Revisión Sistemática Con Metaanálisis] - Aedo-Munoz, E; Brito, C (Federacion Espanola de Docentes de Educacion Fisica, 2024)
This study review and analyze studies that measured the effect of combined strength/power warmup (COMB) versus traditional (TRAD) on the post-activation performance enhancement (PAPE) of swimmers. For this, we performed a systematic review was carried out with meta-analysis based on descriptors related to PAPE in swimming. A total of 138 articles were identified, of which 15 were selected. Comparisons between the COMB condition and the TRAD warm-up were performed for the following set of variables: a) power in 50- and 100-meter events, b) start performance, c) test time of 50- and 100- meters, and d) instantaneous speed in 50-meters events. The data extracted from the studies showed acceptable homogeneity (I2=0.000). When we observed the confidence intervals, it was verified that there were no differences between the COMB condition and the TRAD for power in 50 and 100 m events (Hedges g =-0.12; 95%CI=-0.376; 0.136; p=0.357); time in 50- and 100-meter races (Hedges g =-0.139; 95%CI=-0.314; 0.036; p=0.118); start performance (Hedges g =-0.313; 95%CI =-0.643; 0.018; p=0.064). The COMB condition had an ergogenic effect on instantaneous speed in the 50 m event (Hedges g =-0.282; 95%CI=-0.402; -0.162; p≤0.001). In conclusion, the present meta-analysis concluded that the COMB intervention does not exert an ergogenic effect on the performance of swimmers for the set of analyzed variables, except for instantaneous speed in 50 m events. Future studies may compare other forms of warmup versus the TRAD. © 2024 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.